USP50 regulates NLRP3 inflammasome activation in duodenogastric reflux-induced gastric tumorigenesis - Zhao, Chenye; Mu, Mingchao; Li, Xiaopeng; Dong, Zepeng; Wang, Jiahao; Yao, Chengzhi; Zheng, Jianbao; Sun, Xuejun; Yu, Junhui (Frontiers in Immunology, 2024)
Duodenogastric reflux (DGR) has been linked to the onset of gastric cancer (GC), although the precise mechanism is yet obscure. Herein, we aimed to investigate how refluxed bile acids (BAs) and macrophages are involved in gastric carcinogenesis. In both active human bile reflux gastritis and the murine DGR model, ubiquitin specific protease 50 (USP50) was dramatically raised, and macrophages were the principal leukocyte subset that upregulated USP50 expression. Enhancing USP50 expression amplified bile acid-induced NLR family pyrin domain containing 3 (NLRP3) inflammasome activation and subsequent high-mobility group box protein 1 (HMGB1) release, while USP50 deficiency resulted in the reversed alteration. Mechanistically, USP50 interacted with and deubiquitinated apoptosisassociated speck-like protein containing CARD (ASC) to activate NLRP3 inflammasome. The release of HMGB1 contributes to gastric tumorigenesis by PI3K/AKT and MAPK/ERK pathways. These results may provide new insights into bile reflux-related gastric carcinogenesis and options for the prevention of DGR-associated GC.